Fossombronia bengalensis (Marchantiophyta, Fossombroniaceae)—a new species from West Bengal, India - Islam, Sk. Rasidul; Mondal, Amal Kumar; Singh, Devendra; Cargill, D. Christine (Phytotaxa, 2025)
A new species of the genus Fossombronia, named Fossombronia bengalensis sp. nov., is described from West Bengal, India. This species closely resembles F. stephanii but can be distinguished by a unique combination of features: leaves with shortly decurrent bases, dioicous sexuality, and spores measuring 25–40 µm in diameter with 10–12 reticulations across the distal face, each reticulation internally filled with fine, regular papillae. The discovery of F. bengalensis adds to the known diversity of the genus in India and highlights the region’s bryofloristic richness.